Review on Cyclic Adenosine Monophosphate signaling pathway (cAMP), DLK Signaling Pathway, RAS/RAF Signaling, Retinoic Acid Signaling, Phosphatidylinositol 3-kinase (PI3K) as the Signaling Pathways Involved in Peripheral Neuronal Generation - Ria Margiana (Journal of Global Pharma Technology, 2016)
Neuronal regeneration is the physiological process wear, after neuronal injury, the body stimulates mechanisms of self-healing. Thus, through coordinated different processes and signaling that involves diverse molecules in the body, the nerves are able to regain, to some extent, their initial capability to transduce and convey signals. After, neuronal injury, there is a defect in the normal signal transduction. This presents with different symptoms depending on the system in which the nerve belongs. This may be mortar or sensory. Injury to mortar neurons means the supply of the muscle innervated is cut off. This, therefore, implies that the muscle will not have enough power or will become spastic. It is in response to this injury, that the nerve, through some intricate intrinsic signaling pathways, is able to regenerate in order to return the normal physiologic functioning of the body. Methode of this paper is summed up with systemic reviews of articles in the same topic under study. The articles were searched using the Pubmed search engine and were all in English. None of the articles was translated. The inclusion and exclusion criteria was guided by PRISMA guide, as a predetermined outline. The result of this article is out of forty-three, eight articles were selected as eligible, this is because they met the PRISMA criteria and had adequate relevant and supporting experiments to back the signaling pathway under study.  These articles had a clear and elaborate outline of the whole signaling pathway, the associated molecules, the interconnections between the pathways, supporting experiments and even recommended research in the same field or topic. The comparison of the strengths of facts backing the individual pathways was used to determine the pathway that is most involved, or that can be presumes the “mother” signaling pathway in the process of neuronal regeneration.Keywords: Neuronal regeneration, Neuronal injury, Signaling pathway.